Evaluation of the pandemic and vaccination against COVID-19 in the health of dental academics - Lira, Ana de Lourdes Sá; Campos, Sávio Henrique Lira; Campos, André Vinícius Lira; Carvalho, Breno Wesley Leal; Silva, Elen Maria Carvalho da; Sousa, Emylle Eduarda da Silva (Revista da ABENO, 2022)
This study investigated the prevalence of the coronavirus disease (COVID-19) and vaccination among dental students from public and private institutions, as well as verified the level of influence of the pandemic and vaccination on physical, mental health and academic performance. In this cross-sectional study an online questionnaire using Google Forms® was applied to dental students from a public and a private university on epidemiological data, COVID-19, vaccination and the impact of social distancing on health. The rate of COVID-19 infection in both groups was 36.8% (n=46), and when asked about the period of infection, 82.6% of these (n=38) contracted it before the first dose, but there were no statistically significant differences (χ2=2.667; p=0.102) between the groups. There was a difference between the groups tested, since 56.3% of the students from G1 were vaccinated with a second dose, compared to 29.6% from G2 (χ2= 16.554; p= 0.0009). Students were asked about the existence of risks in the dentistry course, and 76.8% considered that there are risks (n=96), with a statistically significant difference (χ2 =10.216; p= 0.001). Regarding the vaccine, 64% of the participants think it is safe (n=80), with a statistically significant difference between the groups (χ2 = 4.374; p= 0.036). Most students contracted COVID-19 before the first dose, were vaccinated with the second dose by AstraZeneca and Pfizer immunizers. The academic performance and the physical and mental health of the students were significantly affected, with the students of advanced periods and those of public universities suffering more negative impacts.